Zandelisib with continuous or intermittent dosing as monotherapy or in combination with rituximab in patients with relapsed or refractory B-cell malignancy: a multicentre, first-in-patient, dose-escalation and dose-expansion, phase 1b trial. Issue 8 (August 2022) - Pagel, John M; Soumerai, Jacob D; Reddy, Nishitha; Jagadeesh, Deepa; Stathis, Anastasios; Asch, Adam; Salman, Huda; Kenkre, Vaishalee P; Iasonos, Alexia; Llorin-Sangalang, Judith; Li, Joanne; Zelenetz, Andrew D
Summary: Background: Phosphatidylinositol 3-kinase p110δ (PI3Kδ) inhibitors are efficacious in B-cell malignancies. Immune-related adverse events might be mitigated with intermittent dosing. We aimed to evaluate the safety and antitumour activity of zandelisib, a potent novel PI3Kδ inhibitor, with continuous or intermittent dosing as monotherapy or in combination with rituximab, in patients with relapsed or refractory B-cell malignancy. Methods: We conducted a first-in-patient, dose-escalation and dose-expansion, phase 1b trial at ten treatment centres across Switzerland and the USA. Eligible patients were aged 18 years or older with relapsed or refractory B-cell malignancy (limited to follicular lymphoma or chronic lymphocytic leukaemia during dose escalation) and an Eastern Cooperative Oncology Group performance status of 0–2, and had received at least one previous line of therapy and no previous PI3Kδ inhibitor treatment. In the dose-escalation study, participants received oral zandelisib once daily (60 mg, 120 mg, or 180 mg; we did not evaluate four additional planned dose levels). The 60 mg dose was further evaluated as monotherapy or with intravenous rituximab 375 mg/m 2 on days 1, 8, 15, and 22 of cycle 1 and day 1 of cycles 3–6, using a continuous daily schedule or intermittent dosing therapy (days 1–28 of cycles 1–2 and days 1–7 of subsequent cycles) in 28-day cycles. Treatment was continued until evidence of disease progression, intolerance, or withdrawal of consent by the patient. Primary endpoints were safety (dose-limiting toxicities and maximum tolerated dose), minimum biologically effective dose, and a composite endpoint to assess the activity of each dose level, and were analysed by intention to treat. The zandelisib monotherapy and zandelisib–rituximab combination cohorts have completed accrual, but accrual to a cohort evaluating zandelisib with zanubrutinib is ongoing. This study is registered with ClinicalTrials.gov, NCT02914938 . Findings: Between Nov 17, 2016, and June 2, 2020, 100 patients were assessed for eligibility and 97 were enrolled and received zandelisib monotherapy (n=56) or zandelisib plus rituximab (n=41), with zandelisib administered on either a continuous schedule (n=38) or with intermittent dosing (n=59). No dose-limiting toxicities were observed, the objective of determining the maximum tolerated dose was abandoned, and antitumour activity was similar across the evaluated doses activity (objective responses in 11 [92%; 95% CI 61·5–99·8] of 12 patients at both 60 mg and 120 mg doses, and in five [83%; 95% CI 35·9–99·6] of six patients at 180 mg). With a median duration of exposure of 15·2 months (IQR 3·7–21·7), the most common grade 3–4 adverse events were neutrophil count decrease (ten [17%] of 59 patients in the intermittent dosing group and four [11%] of 38 in the continuous dosing group), diarrhoea (three [5%] and eight [21%]), pneumonia (one [2%] and six [16%]), alanine aminotransferase increase (three [5%] and two [5%]), and colitis (two [3%] and one [3%]). 26 (44%) of 59 patients in the intermittent dosing group and 29 (76%) of 38 patients in the continuous dosing group had grade 3–4 adverse events. Treatment-related serious adverse events occurred in eight (21%) patients in the continuous dosing group and five (8%) patients in the intermittent dosing group. There were no treatment-related deaths. Interpretation: Zandelisib 60 mg once daily on an intermittent dosing schedule was safe, with low frequency of grade 3 or worse adverse events, warranting the ongoing global phase 2 and phase 3 trials. Funding: MEI Pharma.